Sanitized for your protection - Pastis, Stephan (Pastis, Stephan. Timmy Failure, 2019)
Timmy Failure finds himself on a cross-country caravan to Chicago with his mother, her boyfriend, and his mother's best friend's family when he learns a secret and tries to discover what it all means.